Healthcare professionals’ understanding of children’s rights: a systematic review of the empirical evidence-base - Sahar Mazied Alshammari; Mark A. Linden; Helen Kerr; Helen Noble (Systematic Reviews)
Abstract Background The concept of children’s rights emerged during the 1980s and emphasised the role of children as active participants in matters which concern them. Aim This review aims to identify and synthesise the empirical evidence base on healthcare professionals’ (HCPs) understanding of children’s rights. Methods Five electronic databases (PubMed, CINAHL, Embase, PsycINFO, and the Web of Science) were systematically searched in May 2023. The Mixed Methods Appraisal Tool (MMAT) was used to quality appraise full-text papers included in the review. A descriptive narrative synthesis of the studies’ findings was performed. Results A total of 15 relevant studies from 10 countries were identified and included in the review. The number of participants included ranged from 6 to 1048 for HCPs with a broad range of sampling methods. Based on the narrative synthesis of the included studies, three main themes were identified: (1) Barriers to implementing children’s rights in healthcare, (2) Factors that contribute to children’s rights implementation, and (3) Study instruments used to measure outcomes. Conclusions HCPs require a better understanding of children’s rights to implement these rights into practice. Listening to children, building trusting relationships with children, and continuing professional development of HCPs could help to address barriers to understanding children’s rights. There is a pressing need for the development of a tool that is capable of tracking changes in the understanding of children’s rights in healthcare environments as efforts to increase awareness become more widely recognised.